2017
DOI: 10.1177/1534508417702063
|View full text |Cite
|
Sign up to set email alerts
|

Language Ability of Students With Emotional Disturbance: Discrepancies Between Teacher Ratings and Direct Assessment

Abstract: Language impairment often goes unidentified in students with behavioral disorders, perhaps in part because different forms of problem behavior deflect adult attention from more subtle language deficits. Therefore, attention to teachers' perception of students' language and behavioral performance is merited. The present study examines agreement between a norm-referenced adult rating scale of language proficiency and a standardized, comprehensive language assessment in a sample of 43 boys identified with emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…The sample and measures used in the current study were different, as we examined preschool children in Head Start (rather than elementary school age children; Petersen et al, 2013) and teacher-rated behavior problems rather than parent-reported behavior problems as was used by Girard et al (2016). Researchers point out that inconsistency of findings may be due to differences across measurement method and source for behavior (Chow & Hollo, 2018; Chow & Wehby, 2017). More research is needed using multiple methods and sources of measurement to examine further the directionality of this relationship in early childhood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample and measures used in the current study were different, as we examined preschool children in Head Start (rather than elementary school age children; Petersen et al, 2013) and teacher-rated behavior problems rather than parent-reported behavior problems as was used by Girard et al (2016). Researchers point out that inconsistency of findings may be due to differences across measurement method and source for behavior (Chow & Hollo, 2018; Chow & Wehby, 2017). More research is needed using multiple methods and sources of measurement to examine further the directionality of this relationship in early childhood.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies with Head Start preschool children document the high level of variance in children’s assessments attributed to teacher rater or classroom differences, rather than children’s individual differences (Waterman, McDermott, Fantuzzo, & Gadsden, 2012). Additional measurement sources and methods such as direct observation should be employed in future studies to measure children’s behavior, as best practices in assessment call for the use of multiple informants as well as methods when assessing children’s behavior in preschool (Chow & Hollo, 2018; Dirks, De Los Reyes, Briggs-Gowan, Cella, & Wakschlag, 2012; Miller et al, 2018; Phillips & Lonigan, 2010). Finally, only gender was examined as a potential moderator in the relationship between language and behavior problems.…”
Section: Discussionmentioning
confidence: 99%
“…This may introduce methodologic biases given differences in the rates of reported versus observed disruptive behaviors 5 and language skills. 41 Additionally, there was shared method variance because both disruptive behavior and language skills were obtained by maternal report. Extension of these findings using performance-based measures, such as direct assessments of language skills and standardized observation of disruptive behavior, 42 is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Teacher ratings may be a better predictor of outcomes that are tied more closely to teachers (e.g., grades) than standardized assessments. In a study comparing language assessments of children with ED, Chow and Hollo (2017) reported meaningful discrepancies between teacher-rated language ability and standardized assessments of language. Teachers were much more likely to underestimate than overestimate the presence of language risk in students with ED.…”
Section: Discussionmentioning
confidence: 99%